Anthropic Settlements’ Impact on the Light-Absorbing Aerosol Concentrations and Heating Rate in the Arctic - Losi N.; Markuszewski P.; Rigler M.; Gregorič A.; Močnik G.; Drozdowska V.; Makuch P.; Zielinski T.; Pakszys P.; Kitowska M.; Cefalì A. M.; Gini I.; et al. (Atmosphere, 2023)
Light-absorbing aerosols (LAA) impact the atmosphere by heating it. Their effect in the Arctic was investigated during two summer Arctic oceanographic campaigns (2018 and 2019) around the Svalbard Archipelago in order to unravel the differences between the Arctic background and the local anthropic settlements. Therefore, the LAA heating rate (HR) was experimentally determined. Both the chemical composition and high-resolution measurements highlighted substantial differences between the Arctic Ocean background (average eBC concentration of 11.7 ± 0.1 ng/m3) and the human settlements, among which the most impacting appeared to be Tromsø and Isfjorden (mean eBC of 99.4 ± 3.1 ng/m3). Consequently, the HR in Isfjorden (8.2 × 10−3 ± 0.3 × 10−3 K/day) was one order of magnitude higher than in the pristine background conditions (0.8 × 10−3 ± 0.9 × 10−5 K/day). Therefore, we conclude that the direct climate impact of local LAA sources on the Arctic atmosphere is not negligible and may rise in the future due to ice retreat and enhanced marine traffic.